Apropiación de las redes sociodigitales por los movimientos sociales: el caso del #MatrimonioIgualitario en México (2022)
This article proposes and implements an approach to understand the appropriation of socio-digital networks by social movements. Social network analysis (SNA) is used to highlight the effects that this method has on the matter, observing that the concern is primarily methodological. Through the case study #MatrimonioIgualitario [#Same-sexmarriage] in Mexico, SNA is applied to identify some of the consequences around appropriation. It is recognized that despite its novelty, there is a progressive and vertiginous advance in the matter, however, the fascination of the instrumentation and the results of the application of the method have obfuscated the realization of more variegated findings. Through its instrumentation and in the methodological dialogue and discussion, it is emphasized that the social networks analysis allows us to account for at least three key processes: structure, significance and symbolic reappropriation. In this way, it contributes to rethinking the approaches to the implications of appropriation and, in general terms, to contribute to the understanding of articulation between movements and socio-digital platforms.